National Security and Sustainable Development: Exploring the Gender Phenomenon for Better Future - Dhungel, Laxmi (Unity Journal, 2021)
An androcentric bias prevails in the research related to the national security and development. Numerous aspects of national security are under discussions; however, many of the policy makers and the practitioners maintain reservation to include the dimension of gender in the Nepali context. Moreover, there is a meager discussion in the inclusion of gender role in the national security. Therefore, this study explores the phenomenon of the gender in the national security of Nepal by bringing the stories of women who are participating themselves in the security sector. Those women who are involved in the security sector have been facing various social, familial, structural challenges. It has elaborated on how the gender spectacle can be incorporated in the security sector to maintain sustainable development. This article primarily aims at exploring the gender dimension in national security framework for development. This paper is based on a series of semi-structured interviews with the women currently engaged in Nepal’s security agencies as well as the literature of security gender and development concepts. Here, the narrative approach is incorporated to bring such challenges. In this discussion, Bourdeau’s theory of habitus is brought into the discussion with the transformative approach